Effects of Different Seed Beds and Intercropping Systems on Weed Growth and Productivity of Sorghum and Sunflower at Badeggi, Central Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2023)
The trial was carried out at the experimental field of National Cereals Research Institute Badeggi during the 2020 and 2021 cropping seasons. The main objective was to determine the effects of different seed beds and intercropping system on weed growth and productivity of Sorghum (Sorghum bicolor) and Sunflower (Helianthus annuus). The different seed beds were: ridge, flat and broad bed while the cropping systems were sole Sorghum, sole Sunflower and Sorghum / Sunflower intercrop. The results showed highest weed density and dry matter/m2 were recorded in sole Sorghum planted on ridge while the least weed density and dry matter/m2 were found in Sorghum /Sunflower intercrop planted on broad bed. Tallest Sorghum plants were recorded when intercropped with Sunflower on flat while the highest Sorghum grain yield was obtained in sole plots planted on broad bed. The height of Sunflower was not affected by both seed bed types and intercrop while the highest and least grain yield of Sunflower were obtained when planted sole on flat and ridge respectively. Planting of Sorghum/Sunflower intercrop on broad bed controlled weed most and sole Sorghum on broad bed gave the highest Sorghum grain yield while maximum Sunflower grain yield was produced in sole planting hence be practiced by farmers